Half-metallic perovskite superlattices with colossal thermoelectric figure of merit - Kahaly, M. Upadhyay; Ozdogan, K.; Schwingenschloegl, U. (ROYAL SOC CHEMISTRY, 2013)
Nowadays heavy experimental efforts are focussed on doped oxide thermoelectrics to increase the thermopower and thermoelectric performance. We propose a high thermoelectric figure of merit for half-metallic SrTi1-xCoxO3 (x = 0, 0.125, 0.25, 0.375, and 0.5) in a superlattice with SrTiO3, which is stable at high temperatures and in an oxygen environment. The maximal value of Z hardly depends on the doping, while the temperature at which the maximum occurs increases with the Co concentration. The easy tunability from being an insulator to a half-metal under substitutional doping combined with the colossal figure of merit opens up great potential in the emerging field of spin-caloritronics.
Keywords: PERFORMANCE; Chemistry; Energy & Fuels; Materials Science